SHIP SINKING POLICY: A LEGAL CHOICE TO ERADICATE ILLEGAL FISHING IN INDONESIA - Faradiba Putri Rahmadani; Agus Triono (Faculty of Law Universitas Lampung, 2022)
Illegal fishing is a serious problem and is detrimental to Indonesia. In overcoming these problem, the Indonesian government has taken several policies including the sinking of ships that do illegal fishing. But this policy raises pros and cons. This article discusses government policies against illegal fishing and ship sinking as an effort to eradicate illegal fishing in Indonesian waters. This article is a normative legal research with a statutory approach. The data was obtained from searching relevant national and international legal materials and analyzed descriptively. The results showed that the government policies related to illegal fishing were carried out in several ways, namely: Formation of Task Force 115, Indonesian Marine Policy, Transshipment Policy and Ship Sinking Policy. The implementation of this policy is very dependent on the legal choice of the minister who is in office. The Ship Sinking Policy is considered as a concrete and decisive action that is far more important and effective than other actions. In addition, the policy of sinking ships is carried out based on sufficient preliminary evidence to avoid conflicts with other countries.